Demography and Localized Reservoirs of Diversity Underlie Global Divergence in the Giant Kelp Macrocystis pyrifera - E. C. Giles; A. Zaiko; H. G. Hampton; P. Saenz‐Agudelo; M. Scriver; D. Crossett; A. Sim; X. B. Zhang; T. Jedrecka; C. O. Blain; L. Rauhina‐August; C. E. Cornwall; et al. (Molecular Ecology, 2026)
Accurate assessments of genetic diversity are crucial for effective management of natural resources. Numerous evolutionary mechanisms and genetic constraints can shape lineage divergence, challenging our quantification of biodiversity. Here, using whole genome resequencing of globally distributed giant kelp, Macrocystis pyrifera (Order: Laminariales), we show clear separation of genetic groups across the Pacific based on 99 genotyped individuals and 799,160 SNPs. Additionally, divergence across 88 genotyped individuals (53 derived in silico and 35 newly sequenced) considering 5,466,408 SNPs is attributed to both historical demographic processes and differential selection. Between Central California and the South Pacific (Chile, Tasmania, New Zealand), high divergence has occurred with very weak levels of gene flow, with concurrent timing of divergence. In parts of the South Pacific, kelp exhibited nucleotide diversity comparable to Central Californian populations but showed stronger signals of directional selection and excesses of rare alleles, with fewer genes showing signs of negative selection and some carbon‐related genes under positive selection. In contrast, Central Californian kelp had an excess of genes with synonymous mutations and showed evidence of a recent population contraction, as indicated by linkage disequilibrium and Tajima's D . In all populations, genome‐wide background divergence was paired with narrow genomic intervals of high nucleotide diversity and high linkage disequilibrium, which predominantly contained pervasive repetitive sequences. These repetitive regions were larger and more often shared among genetic groups in the South Pacific. They also appear to harbour genes of unknown function and alleles at intermediate frequency, suggesting that giant kelp maintain reservoirs of diversity within linked repeats, and this phenomenon is more pronounced in South Pacific M. pyrifera . Overall, the discovery of differential selection and structural variation as key drivers of divergence points to underappreciated genomic mechanisms of adaptation in kelp. These results will be useful for informing efforts to enhance climate resilience by identifying the evolutionary potential underlying kelp forest adaptation in the future.

Gut microplastics of two non-native freshwater fish species, Geophagus altifrons and Cichla orinocensis, in Singapore reservoirs - Xue Shen Teo; Kean Sim Lai; Jeffrey T. B. Kwik; Maxine A. D. Mowe; Darren C. J. Yeo (Aquatic Ecology, 2026)

A targeted correction for arctic oscillation biases in seasonal forecasts - Ji-Han Sim; Baek-Min Kim; Ha-Rim Kim; Gaeun Kim; A-Young Lim; Yoo-Rim Jung; Ju Heon Kim; Geun Young Kim; Steven Cocke (Climate Dynamics, 2026)

Corn Starch/Soybean Wax Double Coated Biochar-based Controlled-release Nitrogen Fertilizer: Water Retention, Release Kinetics and Okra Growth - I. J. X. Yong; I. A. W. Tan; D. H. H. Sim; L. L. P. Lim (Water, Air, & Soil Pollution, 2026)

Diverse prokaryotic strategies associated with soil organic matter priming - M. Waibel; E. Paterson; T.E. Freitag; F. Abram; P.E. Hedley; J. Morris; L.J. Robinson; A. Sim; B. Thornton; F.P. Brennan (Applied Soil Ecology, 2026)

Exposure to traffic-related air pollution and the risk of premature rupture of membranes: a cohort analysis of the Korean CHildren’s ENvironmental health Study (Ko-CHENS) - Dong-Wook Lee; Kyung A. Lee; Jongmin Oh; Hwan-Cheol Kim; Sanghwan Song; Yun-Chul Hong; Eunhee Ha; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; et al. (Environmental Science and Pollution Research, 2026)

Inhibition of Microcystis aeruginosa Kützing by seven submerged macrophytes and the influence of season and decomposing plant leachate - Huy A. Luong; Ann-Marie Rohlfs; Jordan A. Facey; Anne Colville; Darren Z. H. Sim; Simon M. Mitrovic (Hydrobiologia, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Pan‐Arctic Peatlands Have Expanded During Recent Warming - J. Handley; R. E. Fewster; T. G. Sim; S. Hodson; B. Parker; K. Crichton; D. Charman; K. Anderson; M. Garneau; M. Väliranta; D. W. Beilman; G. T. Swindles; et al. (Global Change Biology, 2026)
The fate of carbon stored in Arctic peatlands remains uncertain because of the complex nature of the effects of climate change on permafrost and peatland carbon cycling. Expansion and/or shrinkage of Arctic peatlands under climate change also remain unknown due to lack of ground data and difficulties detecting changes in the extent of these ecosystems, meaning that land surface model predictions currently inadequately quantify Arctic terrestrial carbon storage changes. Pan‐Arctic shifts in peatland extent would profoundly change the fate of carbon in the terrestrial Arctic. Here, we tackle this knowledge gap by answering three main questions: (a) has lateral expansion occurred in Arctic peatlands as a response to recent warming? (b) if so, how fast has this occurred? (c) how does the response vary regionally? To answer these, we collected a dataset (12 peatland sites, 91 peat cores) combining peat cores collected across two latitudinal (north–south) transects: one in the European Arctic and one in the Canadian Arctic. In each region, we selected three peatland sites, with cores collected from transects spanning the peat‐edge to the peat‐centre. Our large‐scale dataset shows that peatlands have expanded, often rapidly, with some rates exceeding ~1 m per year since 1950 AD. This rapid expansion has occurred during a period of widespread Arctic warming and is still ongoing: two thirds (8/12) of our peatland sites evidence new peat formation after ~1990 AD based on age‐depth models constrained by 14 C and 210 Pb dating. Given that our sites comprise a broad range of Arctic conditions, we expect peatland expansion to be a pan‐Arctic phenomenon. Within specific regions, there are constraints on peat expansion including topographical limits, but we present the basis for future work to estimate pan‐Arctic peatland expansion, plus the associated carbon cycle implications under future climate change.

Associations of pre- and postnatal levels of three heavy metals with visual impairment in 3-year-old children - Dajeong Ham; Sung Yeon Kim; Sanghyuk Bae; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; JungHeum Jo; A-Ra Jung; Seung Do Yu; Hyun Jeong Kim; et al. (Environmental Research, 2025)

Automated abdominal aortic calcification scoring from vertebral fracture assessment images and fall-associated hospitalisations: the Manitoba Bone Mineral Density Registry - Marc Sim; Abadi K. Gebre; Jack Dalla Via; Siobhan Reid; Mohammad Jafari Jozani; Douglas Kimelman; Barret A. Monchka; Syed Zulqarnain Gilani; Zaid Ilyas; Cassandra Smith; David Suter; John T. Schousboe; et al. (GeroScience, 2025)
Abdominal aortic calcification (AAC), a subclinical measure of cardiovascular disease (CVD) that can be assessed on vertebral fracture assessment (VFA) images during osteoporosis screening, is reported to be a falls risk factor. A limitation to incorporating AAC clinically is that its scoring requires trained experts and is time-consuming. We examined if our machine learning (ML) algorithm for AAC (ML-AAC24) is associated with a higher fall-associated hospitalisation risk in the Manitoba Bone Mineral Density (BMD) Registry. A total of 8565 individuals (94.0% female, age 75.7 ± 6.8 years) who had a BMD and VFA image from DXA between February 2010 and December 2017 were included. ML-AAC24 was categorised based on established categories (ML-AAC24 = low < 2; moderate 2 to < 6; high ≥ 6). Cox proportional hazards models assessed the relationship between ML-AAC24 categories and incident fall-associated hospitalisations obtained from linked health records (mean ± SD follow-up, 3.9 ± 2.2 years). Individuals with moderate (9.6%) and high ML-AAC24 (11.7%) had a greater proportion of fall-associated hospitalisations, compared to those with low ML-AAC24 (6.0%). In age and sex-adjusted models, compared to low ML-AAC24, moderate (HR 1.49, 95% CI 1.24–1.79) and high ML-AAC24 (HR 1.89, 95% CI 1.56–2.28) were associated with greater hazards for a fall-associated hospitalisation. Results were comparable (HR 1.37, 95% CI 1.13–1.65 and HR 1.60, 95% CI 1.31–1.95, respectively) after multivariable adjustment, including prior falls and CVD, as well as medication use. Integrating ML-AAC24 into bone density machine software to identify high risk individuals would opportunistically provide important information on fall and cardiovascular disease risk to clinicians for evaluation and intervention.

Anomalous temperatures increase occupational injuries, illnesses and associated cost burden in Australia - Matthew A. Borg; Jianjun Xiang; Olga Anikeeva; Bertram Ostendorf; Blesson Varghese; Keith Dear; Dino Pisaniello; Alana Hansen; Kerstin Zander; Malcolm R. Sim; Peng Bi (Urban Climate, 2025)

Prospective life cycle assessment of climate and biodiversity impacts of meat‐based and plant‐forward meals: A case study of Indonesian and German meal options - Sandra G. Marquardt; P. James Joyce; Giles Rigarlsford; Mariska Dötsch‐Klerk; Kathelijn van Elk; Jonathan Doelman; Vassilis Daioglou; Mark A. J. Huijbregts; Sarah Sim (Journal of Industrial Ecology, 2024)
The emerging field of prospective life cycle assessment (pLCA) offers opportunities for evaluating the environmental impacts of possible future consumption shifts. One such shift involves a transition from meat‐based to plant‐forward diets, acknowledged to mitigate environmental impacts of the food system under present day conditions. Current diets are often meat intensive (“meat‐based”), whilst “plant‐forward” diets include mainly plant‐based foods, encompassing flexitarian, vegetarian, and vegan diets. Here we illustrate the application of pLCA in a case study of meal options, implementing shared socio‐economic pathway scenarios in the LCA background system to represent future production conditions. We assess the climate footprints and land‐based biodiversity footprints of a typical meat‐based meal in Germany and Indonesia compared to a plant‐forward meal in both countries (i.e., four meals), now and in 2050. Our findings show that the plant‐forward alternative maintains a lower impact per serving in all future scenarios. At the same time, the reduction in impact for the meat‐based meals is more pronounced in future scenarios due to shifts in the agricultural system. Our findings highlight the importance of supply‐side measures to produce lower‐impact ingredients, complementing demand‐side interventions to reshape food consumption. Results are further evaluated in cultural and nutritional contexts, highlighting the practical decision‐making constraints faced by consumers. We find potential “leakage” effects in calories and nutrition when choosing a lower‐impact, plant‐forward meal. These leakage effects should be considered in future studies seeking to evaluate the environmental implications of meal substitutions in the context of broader dietary requirements.

Nanoneedles like FeP engineered on Ni-Foam as an effective catalyst towards overall alkaline freshwater, urea, and seawater splitting - Anjali Gupta; Cassia A. Allison; Rishabh Srivastava; Anuj Kumar; Mina Sim; Jeffery Horinek; Wang Lin; Felipe M. de Souza; Sanjay R. Mishra; Felio Perez; Ram K. Gupta; Tim Dawsey (Fuel, 2024)

Current and projected heatwave-attributable occupational injuries, illnesses, and associated economic burden in Australia - Matthew A. Borg; Jianjun Xiang; Olga Anikeeva; Bertram Ostendorf; Blesson Varghese; Keith Dear; Dino Pisaniello; Alana Hansen; Kerstin Zander; Malcolm R. Sim; Peng Bi (Environmental Research, 2023)

Land use diversification may mitigate on‐site land use impacts on mammal populations and assemblages - Koen J. J. Kuipers; Sarah Sim; Jelle P. Hilbers; Stefanie K. van den Berg; Melinda M. J. de Jonge; Krista Trendafilova; Mark A. J. Huijbregts; Aafke M. Schipper (Global Change Biology, 2023)
Land use is a major cause of biodiversity decline worldwide. Agricultural and forestry diversification measures, such as the inclusion of natural elements or diversified crop types, may reduce impacts on biodiversity. However, the extent to which such measures may compensate for the negative impacts of land use remains unknown. To fill that gap, we synthesised data from 99 studies that recorded mammal populations or assemblages in natural reference sites and in cropland and forest plantations, with or without diversification measures. We quantified the responses to diversification measures based on individual species abundance, species richness and assemblage intactness as quantified by the mean species abundance indicator. In cropland with natural elements, mammal species abundance and richness were, on average, similar to natural conditions, while in cropland without natural elements they were reduced by 28% and 34%, respectively. We found that mammal species richness was comparable between diversified forest plantations and natural reference sites, and 32% lower in plantations without natural elements. In both cropland and plantations, assemblage intactness was reduced compared with natural reference conditions, but the reduction was smaller if diversification measures were in place. In addition, we found that responses to land use were modified by species traits and environmental context. While habitat specialist populations were reduced in cropland without diversification and in forest plantations, habitat generalists benefited. Furthermore, assemblages were impacted more by land use in tropical regions and landscapes containing a larger share of (semi)natural habitat compared with temperate regions and more converted landscapes. Given that mammal assemblage intactness is reduced also when diversification measures are in place, special attention should be directed to species that suffer from land use impacts. That said, our results suggest potential for reconciling land use and mammal conservation, provided that the diversification measures do not compromise yield.

Grass variety selection of microbial community composition is associated with differences in soil CO2 emissions - M.E. Giles; S. Caul; D. King; S. Mitchell; A. Sim; R. Neilson; E. Paterson (Applied Soil Ecology, 2023)

Agmatine-IRF2BP2 interaction induces M2 phenotype of microglia by increasing IRF2-KLF4 signaling - Jiwon Kim; A Young Sim; Sumit Barua; Jong Youl Kim; Jong Eun Lee (Inflammation Research, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Impact of land cover, rainfall and topography on flood risk in West Java - Rahmawati Rahayu; Simon A. Mathias; Sim Reaney; Gianni Vesuviano; Rusmawan Suwarman; Agus M. Ramdhan (Natural Hazards, 2023)
Flooding represents around 32% of total disasters in Indonesia and disproportionately affects the poorest of communities. The objective of this study was to determine significant statistical differences, in terms of river catchment characteristics, between regions in West Java that reported suffering from flood disasters and those that did not. Catchment characteristics considered included various statistical measures of topography, land-use, soil-type, meteorology and river flow rates. West Java comprises 154 level 9 HydroSHEDS sub-basin regions. We split these regions into those where flood disasters were reported and those where they were not, for the period of 2009 to 2013. Rainfall statistics were derived using the CHIRPS gridded precipitation data package. Statistical estimates of river flow rates, applicable to ungauged catchments, were derived from regionalisation relationships obtained by stepwise linear regression with river flow data from 70 West Javanese gauging stations. We used Kolmogorov–Smirnov tests to identify catchment characteristics that exhibit significant statistical differences between the two sets of regions. Median annual maximum river flow rate (AMRFR) was found to be positively correlated with plantation cover. Reducing plantation land cover from 20 to 10% was found to lead to a modelled 38% reduction in median AMRFR. AMRFR with return periods greater than 10 years were found to be negatively correlated with wetland farming land cover, suggesting that rice paddies play an important role in attenuating extreme river flow events. Nevertheless, the Kolmogorov–Smirnov tests revealed that built land cover is the most important factor defining whether or not an area is likely to report flood disasters in West Java. This is presumably because the more built land cover, the more people available to experience and report flood disasters. Our findings also suggest that more research is needed to understand the important role of plantation cover in aggravating median annual maximum river flow rates and wetland farming cover in mitigating extreme river flow events.

A multi-centre retrospective study of Nocardia speciation and antimicrobial susceptibility in Queensland, Australia - B. Z. Sim; L. Aaron; C. Coulter; J. Parkes-Smith; T. Badrick; K. May; M. Armstrong; S. Hendry; L. Sundac; L. Dang; J. Ho; J. Hanson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Addressing data gaps in marine litter distribution: Citizen science observation of plastics in coastal ecosystems by high-school students - Ana I. Catarino; Edem Mahu; Marine I. Severin; Lazare Kouame Akpetou; Pavanee Annasawmy; Francis Emile Asuquo; Fiona Beckman; Mostapha Benomar; Annette Jaya-Ram; Mohammed Malouli; Jan Mees; Ivanice Monteiro; et al. (Frontiers in Marine Science, 2023)
The Citizen Observation of Local Litter in coastal ECosysTems (COLLECT) project (2021-2022) is a citizen science initiative, supported by the Partnership for Observation of the Global Ocean (POGO), which aimed to acquire distribution and abundance data of coastal plastic litter in seven countries: in Africa (Benin, Cabo Verde, Côte d’Ivoire, Ghana, Morocco, Nigeria) and Asia (Malaysia). In this paper, we describe the workflow used to establish and run this project, as well as the methodologies to acquire data. The COLLECT project consisted of training local students (15 - 18 years old) from ten second cycle institutions (“high schools”) on sampling and analyzing macro-, meso- and microplastics in beach sediments, using a quantitative assessment protocol. We further describe in detail the methodologies applied in assessing the impact of participating in the activities from a social sciences perspective. All documents and materials resulting from this project will be open access and available according to the FAIR Principles (Findable, Accessible, Interoperable, and Reusable). The results and outcomes from COLLECT will contribute to expanding knowledge and establishing baseline information on coastal plastic pollution, with citizen science being an enabler of open science, allowing data to be freely available to the public, academics and policymakers. Expected results from the use of the COLLECT protocol globally will further contribute to the identification of hotspots of coastal plastic litter, and bring awareness to local communities on the potential consequences of plastic pollution. The COLLECT project actively contributes with data suitable to survey plastic litter to the United Nations’ Sustainable Development Goals (UN SDGs), in particular to SDG 14, on the sustainable use of the ocean.

EGR3 regulates opioid-related nociception and motivation in male rats - Swarup Mitra; Shruthi A. Thomas; Jennifer A. Martin; Jamal Williams; Kristen Woodhouse; Ramesh Chandra; Jun Xu Li; Mary Kay Lobo; Fraser J. Sim; David M. Dietz (Psychopharmacology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Tropical macrophytes promote phytoplankton community shifts in lake mesocosms: relevance for lake restoration in warm climates - Darren Z. H. Sim; Maxine A. D. Mowe; Yiluan Song; Joy Lu; Hugh T. W. Tan; Simon M. Mitrovic; Daniel L. Roelke; Darren C. J. Yeo (Hydrobiologia, 2021)

Reparative System Arising from CCR2(+) Monocyte Conversion Attenuates Neuroinflammation Following Ischemic Stroke - Joohyun Park; Jong Youl Kim; Yu Rim Kim; Meiying Huang; Ji Young Chang; A Young Sim; Hosung Jung; Won Taek Lee; Young-Min Hyun; Jong Eun Lee (Translational Stroke Research, 2021)
Monocytes recruitment from the blood to inflamed tissues following ischemic stroke is an important immune response to wound healing and tissue repair. Mouse monocytes can be endogenously divided into two distinct populations: pro-inflammatory or classical monocytes that express CCR2 high CX3CR1 low and circulate in blood, and anti-inflammatory or non-classical monocytes that express CCR2 low CX3CR1 high and patrol locally. In this study of transgenic mice with functional CX3CR1 GFP/+ or CX3CR1 GFP/+ -CCR2 RFP/+ , we found that CCR2 high CX3CR1 low monocytes recruited to the injured brain were cytokine-dependently converted into CCR2 low CX3CR1 high macrophages, especially under the influence of IL-4 and IL-13, thereby attenuating the neuroinflammation following sterile ischemic stroke. The overall data suggest that (1) the regulation of monocyte-switching is one of the ultimate reparative strategies in ischemic stroke, and (2) the adaptation of monocytes in a locally inflamed milieu is vital to alleviating the effects of ischemic stroke through innate immunity.

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

Impact of formulary interventions on the minimum inhibitory concentration of methicillin-resistant Staphylococcus aureus to mupirocin, chlorhexidine, and octenidine in a Singapore tertiary institution - Shuwei Zheng; S. J. Chung; H. C. J. Sim; T. M. Chlebicka; Y. H. Chan; T. P. Lim; L. H. A. Kwa; M. P. Chlebicki (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Kappa opioid receptors mediate an initial aversive component of paclitaxel-induced neuropathy - Julie A. Meade; Y. Alkhlaif; K. M. Contreras; S. Obeng; W. Toma; L. J. Sim-Selley; D. E. Selley; M. I. Damaj (Psychopharmacology, 2020)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Iron considerations for the athlete: a narrative review - Marc Sim; Laura A. Garvican-Lewis; Gregory R. Cox; Andrew Govus; Alannah K. A. McKay; Trent Stellingwerff; Peter Peeling (European Journal of Applied Physiology, 2019)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

An analysis of first-time and repeat visitors to Korean national parks from 2007 and 2013 - Yunseon Choe; Michael A. Schuett; Kyu-Won Sim (Journal of Mountain Science, 2017)

Age estimates of Frullania (Frullaniaceae, Porellales) main lineages: another example of rapid and recent diversification in liverwort evolution - Sara E. Silva; Diogo N. Silva; Tereza Almeida; CÉsar A. Garcia; OctÁvio S. Paulo; Manuela Sim-sim (Systematics and Biodiversity, 2017)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Conservation of Portuguese red-listed bryophytes species in Portugal: Promoting a shift in perspective on climate changes - C. Sérgio; C. A. Garcia; C. Vieira; H. Hespanhol; M. Sim-Sim; S. Stow; R. Figueira (Plant Biosystems, 2014)

Isolation and characterization of 8 polymorphic microsatellite markers from the Greater Short-horned Lizard (Phrynosoma hernandesi) - Zijian Sim; Brandon K. Booker; Michelle Viengkone; Corey S. Davis; Magdalene N.-Y. Leung; Anthony P. Russell; Cynthia A. Paszkowski (Conservation Genetics Resources, 2014)

Snapper ( Chrysophrys auratus ): a review of life history and key vulnerabilities in New Zealand - DM Parsons; CJ Sim‐Smith; M Cryer; MP Francis; B Hartill; EG Jones; A Le Port; M Lowe; J McKenzie; M Morrison; LJ Paul; C Radford; et al. (New Zealand Journal of Marine and Freshwater Research, 2014)
Snapper ( Chrysophrys auratus ) is an important coastal fish species in New Zealand for a variety of reasons, but the large amount of research conducted on snapper has not been reviewed. Here, we review life history information and potential threats for snapper in New Zealand. We present information on snapper life history, defining stages (eggs and larvae, juvenile and adult), and assess potential threats and knowledge gaps. Overall we identify six key points: 1. post‐settlement snapper are highly associated with certain estuarine habitats that are under threat from land‐based stressors. This may serve as a bottleneck for snapper populations; 2. the largest knowledge gaps relate to the eggs and larvae. Additional knowledge may help to anticipate the effects of climate change, which will likely have the greatest influence on these early life stages; 3. ocean acidification, from land‐based sources and from climate change, may be an important threat to larval snapper; 4. a greater understanding of population connectivity would improve certainty around the sustainability of fishery exploitation; 5. the collateral effects of fishing are likely to be relevant to fishery productivity, ecosystem integrity and enduser value; 6. our understanding of the interrelationships between snapper and other ecosystem components is still deficient.

Transcriptional response of Pseudomonas aeruginosa to a phosphate-deficient Lolium perenne rhizosphere - Agnieszka Zyśko; Hervé Sanguin; Andrew Hayes; Leanne Wardleworth; Leo A. H. Zeef; Allan Sim; Eric Paterson; Brajesh K. Singh; Michael A. Kertesz (Plant and Soil, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

∆9-Tetrahydrocannabinol-dependent mice undergoing withdrawal display impaired spatial memory - Laura E. Wise; Stephen A. Varvel; Dana E. Selley; Jason M. Wiebelhaus; Kelly A. Long; Lisa S. Middleton; Laura J. Sim-Selley; Aron H. Lichtman (Psychopharmacology, 2011)

Inhibition of Helicobacter pylori adhesion to Kato III cells by intact and low molecular weight acharan sulfate - Joon-Soo Sim; Bum-Soo Hahn; A-Rang Im; Youmie Park; Ji-Eun Shin; Eun-Ah Bae; Dong-Hyun Kim; Yeong Shik Kim (Glycoconjugate Journal, 2011)

Tree-pulling experiment: an analysis into the mechanical stability of rain trees - Lai Fern Ow; F. R. Harnas; I. G. B. Indrawan; A. Sahadewa; E. K. Sim; H. Rahardjo; E. C. Leong; Y. K. Fong; P. Y. Tan (Trees, 2010)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Molecular, phytochemical and morphological characterization of the liverwort genus Radula in Portugal (mainland, Madeira, Azores) - Michael Stech; Manuela Sim-Sim; M. Glória Esquível; Leena luís; Susana Fontinha; Carlos Lobo; César Garcia; Soraia Martins; Cristiana Vieira; José Barroso; Luis G. Pedro; A. Cristina S. Figueiredo (Systematics and Biodiversity, 2010)

Glycosaminoglycans from earthworms (Eisenia andrei) - A-Rang Im; Youmie Park; Joon-Soo Sim; Zhenqing Zhang; Zhenling Liu; Robert J. Linhardt; Yeong Shik Kim (Glycoconjugate Journal, 2010)

Identification of high-mannose and multiantennary complex-type N-linked glycans containing α-galactose epitopes from Nurse shark IgM heavy chain - David J. Harvey; Max Crispin; Beryl E. Moffatt; Sylvia L. Smith; Robert B. Sim; Pauline M. Rudd; Raymond A. Dwek (Glycoconjugate Journal, 2009)

Expression and Characterization of Human Tissue-Plasminogen Activator in Transgenic Tobacco Plants - Bum-Soo Hahn; Joon-Soo Sim; Hyeong-Mi Kim; Mi-Young Ahn; Hyo-Kyung Pak; Nan-A Kim; Yong-Hwan Kim (Plant Molecular Biology Reporter, 2009)

Pharmacophore based 3D-QSAR study of VEGFR-2 inhibitors - M. M. Neaz; F. A. Pasha; M. Muddassar; So Ha Lee; Taebo Sim; Jung-Mi Hah; Seung Joo Cho (Medicinal Chemistry Research, 2009)

Variation of acharan sulfate and monosaccharide composition and analysis of neutral N-glycans in African giant snail (Achatina fulica) - Youmie Park; Zhenqing Zhang; Tatiana N. Laremore; Boyangzi Li; Joon-Soo Sim; A-Rang Im; Mi Young Ahn; Yeong Shik Kim; Robert J. Linhardt (Glycoconjugate Journal, 2008)

Distribution and symptoms of epiphyte infection in major carrageenophyte-producing farms - Charles S. Vairappan; Chong Sim Chung; A. Q. Hurtado; Flower E. Soya; Genevieve Bleicher Lhonneur; Alan Critchley (Journal of Applied Phycology, 2008)

Ecological regime shifts in salinised wetland systems. I. Salinity thresholds for the loss of submerged macrophytes - Lien L. Sim; Jane M. Chambers; Jenny A. Davis (Hydrobiologia, 2006)

Ecological regime shifts in salinised wetland systems. II. Factors affecting the dominance of benthic microbial communities - Lien L. Sim; Jenny A. Davis; Jane M. Chambers (Hydrobiologia, 2006)

Does chemical composition of individual Scots pine trees determine the biodiversity of their associated ground vegetation? - Glenn R. Iason; Jack J. Lennon; Robin J. Pakeman; Vera Thoss; Joan K. Beaton; David A. Sim; David A. Elston (Ecology Letters, 2005)
Despite plant secondary metabolites being major determinants of species interactions and ecosystem processes, their role in the maintenance of biodiversity has received little attention. In order to investigate the relationship between chemical and biological diversity in a natural ecosystem, we considered the impact of chemical diversity in individual Scots pine trees ( Pinus sylvestris ) on species richness of associated ground vegetation. Scots pine trees show substantial genetically determined constitutive variation between individuals in concentrations of a group of secondary metabolites, the monoterpenes. When the monoterpenes of particular trees were assessed individually, there was no relationship with species richness of associated ground flora. However, the chemical diversity of monoterpenes of individual trees was significantly positively associated with the species richness of the ground vegetation beneath each tree, mainly the result of an effect among the non‐woody vascular plants. This correlation suggests that the chemical diversity of the ecosystem dominant species has an important role in shaping the biodiversity of the associated plant community. The extent and significance of this effect, and its underlying processes require further investigation.

Genetic linkage mapping of an annual × perennial ryegrass population - S. E. Warnke; R. E. Barker; Geunhwa Jung; Sung-Chur Sim; M. A. Rouf Mian; M. C. Saha; L. A. Brilman; M. P. Dupal; J. W. Forster (Theoretical and Applied Genetics, 2004)

Molecular evolutionary analysis of the widespread piggyBac transposon family and related "domesticated" sequences - A. Sarkar; C. Sim; Y. S. Hong; J. R. Hogan; M. J. Fraser; H. M. Robertson; F. H. Collins (Molecular Genetics and Genomics, 2003)

Construction of a BAC library and generation of BAC end sequence-tagged connectors for genome sequencing of the African malaria mosquito Anopheles gambiae - Y. S. Hong; J. R. Hogan; X. Wang; A. Sarkar; C. Sim; B. J. Loftus; C. Ren; E. R. Huff; J. L. Carlile; K. Black; H.-B. Zhang; M. J. Gardner; et al. (Molecular Genetics and Genomics, 2003)

Establishing the Link between Ammonia Emission Control and Measurements of Reduced Nitrogen Concentrations and Deposition - Mark A. Sutton; Willem A. H. Asman; Thomas Ellermann; J. A. Van Jaarsveld; Karin Acker; Viney Aneja; Jan Duyzer; Laszlo Horvath; Sergey Paramonov; Marta Mitosinkova; Y. Sim Tang; Beat Achermann; et al. (Environmental Monitoring and Assessment, 2003)

Respiratory symptoms and lung-function changes with exposure to five substances in aluminium smelters - Lin Fritschi; Malcolm R. Sim; Andrew Forbes; Michael J. Abramson; Geza Benke; William A. Musk; Nicholas H. de Klerk (International Archives of Occupational and Environmental Health, 2003)

Analysis of 15 primary open-angle glaucoma families from Australia identifies a founder effect for the Q368STOP mutation of myocilin - Paul N. Baird; Jamie E. Craig; Andrea J. Richardson; Maree A. Ring; Pamela Sim; Sue Stanwix; Simon J. Foote; David A. Mackey (Human Genetics, 2003)

Seasonal variability of apoplastic NH4 + and pH in an intensively managed grassland - Benjamin Loubet; Celia Milford; Paul W. Hill; Y. Sim Tang; Pierre Cellier; Mark A. Sutton (Plant and Soil, 2002)

Respiratory symptoms and lung function in bauxite miners - Jeremy R. Beach; Nicholas H. de Klerk; Lin Fritschi; Malcolm R. Sim; A. William Musk; Geza Benke; Michael J. Abramson; John J. McNeil (International Archives of Occupational and Environmental Health, 2001)

Small (SK Ca ) Ca 2+ -activated K + channels in cultured rat hippocampal pyramidal neurones - A. A. Selyanko; J. A. Sim; D. A. Brown (Pflügers Archiv - European Journal of Physiology, 1998)

Regulation of desmosomal cell adhesion in human tumour cells by polyunsaturated fatty acids - Wen G. Jiang; Sim K. Singhrao; Stephen Hiscox; Maurice B. Hallett; Richard P. Bryce; David F. Horrobin; Malcolm C. A. Puntis; Robert E. Mansel (Clinical & Experimental Metastasis, 1997)

Uptake and transport of phosphorus by Agrostis capillaris seedlings from rapidly hydrolysed organic sources extracted from32 P-labelled bacterial cultures - A.E.S. Macklon; S.J. Grayston; C.A. Shand; A. Sim; S. Sellars; B.G. Ord (Plant and Soil, 1997)

Linear and nonlinear stiffness and friction in biological rhythmic movements - P. J. Beek; R. C. Schmidt; A. W. Morris; M. -Y. Sim; M. T. Turvey (Biological Cybernetics, 1995)